Percutaneous Catheter Ablation of Epicardial Accessory Pathways. - Sternick EB, EB (2017)
Radiofrequency (RF) catheter ablation is the treatment of choice in patients with accessory pathways (APs) and Wolff-Parkinson-White syndrome. Endocardial catheter ablation has limitations, including the inability to map and ablate intramural or subepicardial APs. Some of these difficulties can be overcome using an epicardial approach performed through the epicardial venous system or by percutaneous catheterisation of the pericardial space. When a suspected left inferior or infero-paraseptal AP is refractory to ablation or no early activation is found at the endocardium, a transvenous approach via the coronary sinus is warranted because such epicardial pathways can be in close proximity to the coronary venous system. Associated congenital abnormalities, such as right atrial appendage, right ventricle diverticulum, coronary sinus diverticulum and absence of coronary sinus ostium, may also hamper a successful outcome. Percutaneous epicardial subxiphoid approach should be considered when endocardial or transvenous mapping and ablation fails. Epicardial mapping may be successful. It can guide and enhance the effectiveness of endocardial ablation. The finding of no epicardial early activation leads to a more persistent new endocardial attempt. When both endocardial and epicardial ablation are unsuccessful, open-chest surgery is the only option to eliminate the AP.